Inflammatory myopathy following coronavirus disease 2019 vaccination: A systematic review - Ding, Yukang; Ge, Yongpeng (Frontiers in Public Health, 2022)
Introduction: Reports of unexpected side effects have accompanied the vaccination of larger proportions of the population against coronavirus disease 2019 (COVID-19), including a few cases of inflammatory myopathy (IM). In a bid to improve understanding of the clinical course of vaccine complications, a systematic review of reported cases of IM following COVID-19 vaccination has been conducted. Methods: The PRISMA guideline 2020 was followed. Two independent investigators systematically searched PubMed and Embase to identify relevant studies published up to July 2022, using the following keywords: COVID-19 Vaccine, inflammatory myositis. The Joanna Briggs Institute critical appraisal tools were used for the risk of bias. Results: A total of 24 articles presenting clinical features of 37 patients with IM following COVID-19 vaccine were identified. Female patients composed 59.5% of cases and 82.4% had been vaccinated with BNT162b2 or ChAdOx1. Onset of symptoms occurred within 2 weeks of the first or second vaccine dose in 29 (85.3%) patients and included muscular weakness in 54.1% and skin rash in 71.4% of patients. Myositis specific autoantibodies (MSAs) and myositis associated autoantibodies (MAAs) were reported in 28 patients. Specific clinical subtypes of myositis, reported in 27 patients, included 22 (81.5%) cases of dermatomyositis (DM) and 3 (11.1%) cases of immune-mediated necrotizing myopathy (IMNM). Following treatment, 32 (86.5%) patients showed improvement on follow-up. Conclusion: COVID-19 vaccine may induce various clinical myositis subtypes and related antibodies. Muscular weakness was the most common presenting symptom. Clinicians should be aware of this unexpected adverse event following COVID-19 vaccination and arrange for appropriate management.